A SuperLEphilic/Superhydrophobic and Thermostable Separator Based on Silicone Nanofilaments for Li Metal Batteries - Yang, Yanfei (iScience, 2019)
Conventional polyolefin separators suffer from poor wettability to liquid electrolytes (LEs). Although some modified separators exhibit improved wettability, they are hydrophilic, causing inevitable moisture uptake. Trace water could result in poor performance and safety hazard of Li metal batteries. Here, we report a design idea of superLEphilic/superhydrophobic and thermostable separators by modifying the Celgard separator using silicone nanofilaments. The separator features low moisture uptake (∼0%), fast LE diffusion (454 ms), and high LE uptake (287.8%), LE retention rate, and Li(+) conductivity. Consequently, the Li/LiFePO(4) cells show high cycling stability (96.05% after 350 cycles), good rate performance (125 mA h g(−1) at 5.0 C), low resistance, and stable open circuit voltage at 160°C. Moreover, the separator could improve performance of the other Li metal batteries with high-voltage cathodes and the LiFePO(4)/graphite pouch cells. This work provides an avenue for designing advanced separators by using bioinspired superwetting surfaces.